Microbial community structure and niche differentiation under different health statuses of Pinus bungeana in the Xiong'an New Area in China - Yang, Jia; Masoudi, Abolfazl; Li, Hao; Gu, Yifan; Wang, Can; Wang, Min; Yu, Zhijun; Liu, Jingze (Frontiers in Microbiology, 2022)
Pinus bungeana is a native but endangered plant species in China, with high ornamental value and adaptability to drought and cold. The relationship between the soil community structure and the endophytic microbes in the tissues of P. bungeana under different health statuses is poorly understood. In this study, the endophytic bacterial and fungal communities of P. bungeana under different health statuses were compared and analyzed in the Xiong'an New Area. Using high-throughput deep sequencing (16S and ITS (Internal Transcribed Spacer) rRNA) techniques, the effect of the health status of P. bungeana on the microbial communities in bulk soil, rhizospheric soil, roots, stems, and leaves was determined in this study. We observed that the diversity of the bacterial and fungal communities of the above-ground parts (stems and leaves) of healthy P. bungeana plants was much higher than that of the unhealthy plants. However, the bacterial and fungal diversity in the below-ground parts (bulk soil, rhizospheric soil, and roots) showed almost no difference in microbial community richness, indicating that the possible cause of the illness was transmitted in a “top to down” manner. Furthermore, there were significant differences in the microbial diversity and community structure in different ecological niches of P. bungeana (P < 0.01). Proteobacteria and Actinobacteria were the dominant bacterial phyla, while Ascomycota, Basidiomycota, and Mortierellomycota were the predominant fungal phyla. Redundancy analysis (RDA) revealed that soil organic matter (SOM), total phosphorous (TP), total potassium (TK), total nitrogen (TN), water content (WC), power of hydrogen (pH), total carbon (TC), and the ratio of carbon to nitrogen (C/N) were significantly correlated with the composition of the microbial communities. Altogether, these results provide a scientific basis for further studies on the mechanism underlying the “above-ground–underground” microbial interactions in plantation forests, which can aid in promoting the healthy and sustainable development of the Millennium Xiulin forest in the Xiong'an New Area.